Selected temperamental properties and achievement motivation of fencers - Gracz, J.; Tomczak, M. (Studies in Physical Culture and Tourism, 2008)
The goal of this study was to characterize the temperamental properties (i.e. reactivity, mobility of nervous processes, the strength of the braking process) and achievement motivation of competitive fencers, inclusive of defining interconnections between these variables. 116 competitive fencers aged 14 to 32 participated in the study (41 of whom have been members of a select national team in their age groups). It has been found that the subjects were marked by a relatively low level of reactivity, a high level of mobility of nervous processes, a comparatively high level of strength of the braking process and an average level of achievement motivation. The statistical analysis also revealed that a low reactivity and a high level of mobility of nervous processes of fencers favored a high achievement motivation. The conclusions drawn from this study allow us to formulate the practical recommendations related to the fencer`s training process that were also presented in this survey.